Controlled S-Metric-Type Spaces and Applications to Fractional Integrals - Ekiz Yazici, Nilay; Ege, Ozgur; Mlaiki, Nabil; Mukheimer, Aiman (Mdpi, 2023)
In this paper, we introduce controlled S-metric-type spaces and give some of their properties and examples. Moreover, we prove the Banach fixed point theorem and a more general fixed point theorem in this new space. Finally, using the new results, we give two applications on Riemann-Liouville fractional integrals and Atangana-Baleanu fractional integrals.
Keywords: fixed point; S-metric; controlled metric type; fractional integral